Prevalence of Risk Factors for Thyroid Hormone Imbalance - Saleha Sadeeqa; Amna Zaka; Iram Arif; Maham Saba Nasir; Pakiza Bint Zakreya; Fatima Amin (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
This study was aimed to assess the frequency of thyroid hormone imbalance risk factors. A cross-sectional survey was conducted using the convenience sampling technique, from July-2018 to September-2018 in different cities of Punjab, Pakistan. A total of 150 patients, having thyroid hormone imbalance with or without any comorbidity were included and the subjects having normal thyroid levels were excluded. Thyroid hormone imbalance was more frequent in females having 40-60 years of age. Gender was significantly associated with 'pregnancy or delivery in last six months' (p=0.029) and iodine deficiency (p=0.036). Marital status was significantly associated with 'symptoms observed' (p=0.009), 'radioactive iodine exposure' (p=0.001), 'autoimmune disease' (p=0.050), 'smoking' (p=0.014) and 'stress' (p=0.040). Family income was significantly associated with 'family history of disease' (p=0.039) and 'iodine deficiency' (p=0.049). Residential area was significantly associated with 'autoimmune disease' (p=0.050), 'smoking' (p=0.036) and 'stress' (p=0.029). Use of iodized salt and stress were prevalent risk factors and disease was common among females, especially age group 40-60 years.